Calendar of Events. (Communications of the ACM, 2015)
A calendar of events related to computer science around the world in the month of April 2015 is presented. Events include "CPS Week '15: Cyber Physical Systems Week 2015" taking place April 13-16, 2015 in Seattle, Washington; the "Symposium on Applied Computing" taking place April 13-17, 2015 in Salamanca, Spain; and the "HSCC '15: 18th International Conference on Hybrid Systems: Computation and Control" taking place April 14-16, 2015 in Seattle, Washington.